Variabilidade genética de Prochilodus lineatus (Characiformes, Prochilodontidae) na bacia do rio Paraná evidenciadas por marcadores moleculares. - Revaldaves, Eloísa (2001)
Overfishing, pollution and construction of dams have impacted migratory fishes of Paraná River basin. Prochilodus lineatus is an economically important endemic migratory species from Platina basin. Decrease in P. lineatus landings have been observed as the need of management and conservation. This study aimed to investigate the genetic variability of this species through Random Amplified Polymorphic DNA (RAPD) and mtDNA sequencing techniques. The analyzed individuals were collected in the Paraná, Bahia, Corumbá and Miranda Rivers. A total of 1815 base pairs from 12 individuals were sequenced to seven PCRAmplified fragments representing five protein-coding mitochondrial genes. Estimates of percent nucleotide sequence divergence ranged from 0.00 to 0.95 and any geographic pattern to mtDNA haplotype distribution was observed. The RAPD study included 86 markers and 58 individuals and revealed a high level of polymorphism. Fisher?s exact test was computed to verify whether the genetic differences were significant for the total data and between geographically proximate population samples. The results suggest that Prochilodus lineatus is not genetically subdivided, although significant divergence in frequencies of some RAPD fragments was found. This information may have useful for stocking and management programs plannings of P. lineatus.